2020
DOI: 10.1002/ppul.24752
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of delivered distending pressures in the oropharynx in preterm infant on bubble CPAP and on three different nasal interfaces

Abstract: Objective To compare the level of continuous positive airway pressure (CPAP) delivered by three different CPAP delivery interfaces (RAM cannula system, Hudson prongs, and nasal mask) in preterm neonates with respiratory distress. Methods Preterm neonates with gestation between 28 weeks and 34 weeks and birth weight more than or equal to 1000 g and requiring nasal CPAP for respiratory distress were eligible for the study. During the study period, consecutive infants requiring CPAP were started on Hudson prongs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
15
0
3
Order By: Relevance
“…Nowadays, RAM® cannula is becoming increasingly common in NICUs to deliver NCPAP and NIPPV 19 . In preterm infants requiring NCPAP for respiratory distress, with a set CPAP of 5 or 6 cmH 2 O, the pharyngeal pressure was consistently lower with the RAM® cannula than with Hudson prongs 9,10 and nasal mask 10 …”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, RAM® cannula is becoming increasingly common in NICUs to deliver NCPAP and NIPPV 19 . In preterm infants requiring NCPAP for respiratory distress, with a set CPAP of 5 or 6 cmH 2 O, the pharyngeal pressure was consistently lower with the RAM® cannula than with Hudson prongs 9,10 and nasal mask 10 …”
Section: Discussionmentioning
confidence: 99%
“…Matlock et al noted that NIPPV with RAM cannula produced clinically insignificant tidal volumes in preterm neonates between 24 and 34 weeks during non-spontaneous inflations 20 . Sharma et al compared the pressures delivered by three different nasal interfaces (nasal mask, Hudson prong, RAM cannula) on 30 neonates in each group with gestation 28–34 weeks and birth weight ≥ 1000 g in our centre, during this study period 21 . We found that none of the nasal interfaces delivered oropharyngeal pressures equivalent to set CPAP pressures.…”
Section: Discussionmentioning
confidence: 99%
“…As in all DILCs, the highest resistance of the Sync‐flow Cannula® is at the level of the two nasal prongs, and this resistance increases in proportion to the length and diameter of the two long connecting tubes. So, comparing a SBP with a DILC with the two small prongs of the same diameter and length, the first will always have a lower resistance 33 . However, with the Sync‐Flow Cannula®, the gas flowing out of the prongs guarantees sufficient flow to support spontaneous breathing, thanks to the low resistance of the connecting tubes, considering that the peak‐flow of a VLBW infant is in the range of 20–50 ml/kg/Sections (1.2–3 L/kg/min) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…So, comparing a SBP with a DILC with the two small prongs of the same diameter and length, the first will always have a lower resistance. 33 Note: The ventilation of four premature infants with an increasing weight (500, 1000, 1500, and 2000 g) was simulated with different PIP settings (15-20-25 mbar) and a flow of 8-10 L/min. The ventilation was performed with 30% leaks at the prongs, with different ITs (0.3-0.5 s) and different compliances, of which the lowest corresponds to a moderate-tosevere RDS (0.5 ml/cmH 2 O) and the highest to a mild RDS (1 ml/cm H 2 O/kg).…”
Section: Discussionmentioning
confidence: 99%